Colonial Codification of Education in India until 1920 - Preeti, (JOURNAL OF INDIAN EDUCATION, 2016)
This paper seeks to understand the nature of colonialism and the nuances of education provided by it through the lens of curricular knowledge in social and natural sciences and technical education till 1920. The British Indian education is conceived in India as an act of securing and consolidating power. By the introduction of the ‘complete system of education’, the British sidelined indigenous education which was marked by diversity. Certificates and exams became ‘a guarantee for high ability and valuable attainments’. The realignment of education brought consent to the British rule which the military power could not have achieved. The Indian subjects were informed that colonial education aimed at bringing ‘modernity’ among the natives. But in the garb of bringing ‘modernity’, it brought a culture of certificates, marksheets and medals which became the prized possessions of ‘haves’. The major social function which colonial education fulfilled was to differentiate the ‘haves’ from the overwhelming majority of ‘have-nots’. However, Indians were not meek spectators either. Several Indian intellectuals set up their own model schools. Active demands put up by the Indian leaders to have more technical colleges attest to Indian participation in education. Therefore, no simple model or statement can be devised to understand why colonial education had the kind of effects it had.